Reassignment of lioestheria codoensis cardoso (spinicaudata, anthronestheriidae) from the Lower Cretaceous of Brazil: systematics and paleoecology - Gallego, Oscar Florencio (2013)
Lioestheria codoensis Cardoso was described from materials originally collected from the Codó Formation (Lower Cretaceous, Parnaíba Basin, Piauí State), northeastern Brazil. Since its discovery L. codoensis has been assigned to different genera by different authors [as Estheriina (Nudusia) and Cyzicus (Lioestheria)]. In this paper, previous systematic assignments are reviewed and discussed in light of new scanning electron microscopy studies of new material. As a result of this research, the species is assigned to a new genus of the Family Antronestheriidae, and the study integrates palaeontological, biological and ecological approaches to provide a robust description for the species. Previous assignments to other genera (Estheriina, Lioestheria and Cyzicus) are also assessed and comparisons with other related genera of the Family Anthronestheriidae(Pseudestherites, Etmosestheria, Anthronestheria and Paleolepthestheria? chinensis) are made. Detailed stratigraphical (Codó, Santana, Itapecuru, Rio da Batateira and Missão Velha formations) and geographical (seven localities) records are compiled. Finally, the autecology and within-species morphological variation are also addressed.